Policy Proposal For Removal Of Regional Property Based On Budget Costs And Realization At The Regional Inspectorate Of Tegal City - Fiyya Alfu Mazaya; Bagus Panuntun (Cita konsultindo, 2025)
The Tegal City Regional Inspectorate is a government agency that has a mandate to supervise the performance of the Regional Government organization. One of them is in verifying Regional Property. Regional Property itself is an asset obtained from the APBD or other legal acquisitions, in the management of BMD there is a budgeting and deletion process. Each region has its own regional assets which are important resources for its government, as is the case with Tegal City. Therefore, it is very important for the government to manage every existing asset adequately. The Tegal City Regional Inspectorate has challenges in deleting Regional Property. The research method uses qualitative with data in the form of observations, interviews, and SKPD PPA Documents. The results of the study indicate that the Tegal City Regional Inspectorate needs to make policies regarding BMD management, especially in its deletion, utilize SIMDA-BMD in BMD data collection, and conduct evaluations and audits of the deletion process.